Strategic communication and barriers to strategy implementation - Durão, Tomás Branco Gaspar Pires (2017)
This dissertation aims to understand and identify the barriers to strategic implementation, focusing, then, through an inquiry, in one of them, to make a deeper analysis of one of the variables. To that end, this document begins by exploring what the concept of strategic management consists of, contextualizing history on this theme - from the 1950s to the present - and analyzing all its steps and processes - especially the moment of formulation, implementation and evaluation and control. Subsequently, based on a poem and an interesting time from a cultural and communicational point of view, one begins to identify the importance that strategic communication has in the process of propagating a given individual idea or, in the terms that interests us most, within of an organization - whether ascending or descending, horizontal or vertical. In the organizational arena, business and communication are two inseparable issues. The last point ends with the connection to the most important part of these lines: the barriers to strategic implementation. In this part, it is explained more deeply in what this moment consists in its variances of application and it is immersed in the multiple possibilities that can cause the collapse of the plans orchestrated by the companies and the main responsible ones. In the end, as a theoretical complement, a questionnaire was designed for a relatively large number of people who were confronted with the topics under discussion throughout this dissertation.